2014
DOI: 10.7705/biomedica.v35i1.2195
|View full text |Cite
|
Sign up to set email alerts
|

Descripción de un brote epidémico de malaria en una comunidad indígena asentada en la zona urbana de Armenia, Quindío. Colombia 2012

Abstract: Contribución de los autores:Liliana Quintero: asesoría de la revisión, corrección del manuscrito e ideas para la discusión Jhon Carlos Castaño: revisión de la literatura científica y redacción del manuscrito Magda Beatriz López y Harold Ramírez: participación en la fase de campo y en la elaboración del informe de estas actividades que sirvió de base para la redacción del manuscrito Introducción. La malaria o paludismo es la enfermedad parasitaria transmitida por mosquitos vectores más frecuente en las regiones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…In this locality, 92% of malaria cases reported in the study period were due to P. vivax. In previous studies, immature stages have been reported breeding in rainwater ponds, lagoons, backwaters of streams, and arti cial water deposits, as well as in animal footprints with accumulated rainwater (41) . However, larvae of this species were not collected in the bodies of water sampled in this study.…”
Section: Discussionmentioning
confidence: 91%
“…In this locality, 92% of malaria cases reported in the study period were due to P. vivax. In previous studies, immature stages have been reported breeding in rainwater ponds, lagoons, backwaters of streams, and arti cial water deposits, as well as in animal footprints with accumulated rainwater (41) . However, larvae of this species were not collected in the bodies of water sampled in this study.…”
Section: Discussionmentioning
confidence: 91%
“…El descenso en la notificación de los casos al Sivigila en el periodo evaluado podría atribuirse a un subregistro y a la ausencia del reporte porque la vigilancia epidemiológica es pasiva (18). En un estudio de captura y recaptura, se evidenció un subregistro del 80 % en la notificación de este evento (19), lo que subraya la necesidad de mejorar los procesos de capacitación del personal encargado de la recopilación de datos, mediante la implementación de cursos regulares, el fortalecimiento de los procedimientos de sensibilización y la presentación oportuna de informes (20).…”
Section: Discussionunclassified
“…Thus establishing a robust health surveillance system to monitor disease, population size, and vulnerability in these populations is warranted in order to prevent a niche of malarial transmission infection by the parasite becoming endemic. Moreover, a further understanding of the distribution of disease in peri-urban areas across ethinic groups should be explored in future research, as some research has already shown that social-ecological factors in peri-urban areas may exacerbate health issues such as malaria and parasite infections in children among Indigenous populations [33,61,62] .…”
Section: Discussionmentioning
confidence: 99%